Development of fundamental function toolbox for image processing and analysis - Jiang, Shan Jiao (2008)
A fundamental function toolbox for image processing and analysis was developed in the project to provide an alternate way, C++ version, of matrix operations which is usually provided by Matlab for image processing and analysis. As the objective of this project is to emulate Matlab relevant function, the function names remain either the same as Matlab or similar to that.